2022
DOI: 10.3389/fanim.2022.972868
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinoacetic acid supplementation: A narrative review of its metabolism and effects in swine and poultry

Abstract: Guanidinoacetic acid (GAA) is an amino acid derivative and precursor for creatine which plays a significant role in energy metabolism. However, because of creatine’s instability during the manufacturing process and cost, GAA has been explored as an effective alternative to creatine supplements. GAA has been tested as a potential feed additive to enhance energy utilization and growth performance in the poultry and swine industries. Moreover, GAA has been combined with methionine to improve growth outcomes and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Besides its role in the gut, it has been demonstrated that GAA is a beneficial and safe dietary supplement in humans and animals. Among its many demonstrated benefits, GAA, likely via conversion to creatine, promotes growth, physical performance, reproductive parameters, and meat quality in commercial animals [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides its role in the gut, it has been demonstrated that GAA is a beneficial and safe dietary supplement in humans and animals. Among its many demonstrated benefits, GAA, likely via conversion to creatine, promotes growth, physical performance, reproductive parameters, and meat quality in commercial animals [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GAA also seems to have several beneficial noncreatine roles in cellular metabolism. For example, GAA can directly or indirectly affect endocrine functions, neuromodulation, and oxidant–antioxidant processes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the growing demand for poultry products, the use of food additives that favor muscle growth and the development of birds, including secondary metabolites, probiotics, prebiotics, and antimicrobial peptides (AMPs), among others, has increased [ 2 ]. Among these alternatives is guanidinoacetic acid (GAA), the natural precursor of creatine (Cr), which is synthesized from arginine and glycine in organs such as the kidneys, pancreas, liver, endocrine tissues, and skin [ 3 , 4 ]. The main function of GAA is to optimize energy use, which is achieved through the efficient conversion of Cr.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that GAA, as a feed additive, has considerable potential to improve production performance, thereby improving the quality of beef [ 6 ] and poultry [ 3 ]. The catabolism of GAA occurs in the small intestine via the action of pancreatic enzymes such as trypsin and elastase in conjunction with dipeptidases produced at the border of the intestinal barrier, releasing arginine and glycine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation